PENYALAHGUNAAN PENGUASAAN PASAR TERHADAP PELAKU USAHA LAIN DI PELABUHAN YOS SUDARSO AMBON BERDASARKAN HUKUM PERSAINGAN USAHA: - Kemal Kusuma Wardana; Anna Maria Tri Anggraini (Reformasi Hukum Trisakti, 2023)
The activities carried out by PT Pelabuhan Indonesia (Persero) constitute a violation of Article 19 Letters a and b of Law Number 5 of 1999 concerning Prohibition of Monopoly Practices and Unfair Business Competition. The formulation of the problem in this research is the form of abuse of market control carried out by PT Pelabuhan Indonesia (Persero) according to Article 19 of Law Number 5 of 1999 concerning Prohibition of Monopoly Practices and Unfair Business Competition and how the KPPU applies whether there are violations of Article 19 of Law 5 /1999 in KPPU Case Decision No. 29/KPPU-L/2020. This research uses a descriptive type of normative research, with secondary data obtained by literature study. The results of the research, discussion and conclusions in this research are that PT Pelabuhan Indonesia abuses market control in the form of circulars aimed at taking over loading and unloading activities carried out by other business actors operating at the port. The circular letter made by PT Pelabuhan Indonesia has no basis and is not binding, so the letter is purely an initiative of PT Pelabuhan Indonesia to make it. KPPU does not have strong evidence so PT Pelabuhan Indonesia declared not to have violated.